The Implementation of the Tahsin Binnadhor Method in Quranic Education at an Islamic Boarding School - Aditya, D. Irza; Dasuki, Moh.; Haruna, Haruna Abu Bakar (IJIBS, 2024)
Implementing the Tahsin Binnadhor method in Qur'anic learning has become a critical issue amidst the need to improve the quality of Qur'anic recitation according to tajwid and tartil principles, particularly in Islamic boarding schools (pesantren). Previous studies have discussed various approaches to Qur'anic learning but have yet to explore the application of the Tahsin Binnadhor method at Pesantren Hubbul Qur'an Yassalam, especially in systematically and comprehensively building reading competencies. This study aims to examine the application of the Tahsin Binnadhor method in improving Qur'anic reading skills at Pesantren Hubbul Qur'an Yassalam, Jombang, East Java. A qualitative approach with a case study method was employed. Data were collected through in-depth interviews, direct observations, and document analysis related to the Qur'anic learning process at the pesantren. The data were analyzed using descriptive-analytical techniques to identify patterns and the effectiveness of the applied method. The findings reveal that the Tahsin Binnadhor method significantly enhances the accuracy of students' recitation in line with tajwid rules and facilitates a more structured learning process. Additionally, integrating this method with traditional pesantren approaches creates a compelling and adaptive learning environment that meets students' needs. In conclusion, implementing the Tahsin Binnadhor method significantly contributes to Qur'anic learning in pesantren, making it a relevant model for similar contexts. This study recommends further development of the process to strengthen its implementation across various pesantren.